Choosing an Investment Program among Interdependent Projects - Reiter, Stanley (Review of Economic Studies, 1963)
Journal Article Choosing an Investment Program among Interdependent Projects Get access Stanley Reiter Stanley Reiter Lafayette, Indiana Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 1, February 1963, Pages 32–36, https://doi.org/10.2307/2296028 Published: 01 February 1963